Metabolic syndrome and serum ferritin level in postmenopausal women in urban cities in Enugu State, Nigeria - Chukwukelu, Ekene E.; Ezeanyika, Lawrence U.S.; Onyia-Pat, Jane E.; Okafor, Edwin N. (International Journal of Scientific Reports, 2016)
Background: Physiological and biochemical changes that alter the general health of women are seen in menopause which include increase in adiposity and elevated serum ferritin. There is a dearth of information on the prevalence and common risk factors of MS and their association with iron stores of the body among postmenopausal women (POMW) in Enugu. Hence, this study was carried out to determine the prevalence of metabolic syndrome, the most prevalent components of metabolic syndrome and its relationship with serum ferritin level in postmenopausal women in Enugu, Nigeria. Methods: The study was a cross sectional study, carried out from February to August 2013 among two hundred and twenty four (224) apparently healthy postmenopausal women aged 40 to 83 years. Metabolic syndrome was defined using National Cholesterol Education Programme, Adult Treatment Panel III criteria. Results: The most frequent components of metabolic syndrome (MS) seen among the subjects were high waist circumference (WC) (70.1%), high blood pressure (66.5%) and low high density lipoprotein cholesterol (25.4%). The prevalence of metabolic syndrome among the women was 29.0% while the mean level of serum ferritin of subjects with metabolic syndrome showed no significant (p >0.05) difference when compared to subjects without MS. Conclusions: The most frequent cluster of the risk factor of MS in the population studied was high WC, high blood pressure and low high density lipoprotein cholesterol (HDL). Although serum ferritin is slightly associated with FPG and WHR, it may not be used as diagnostic tool for MS in the group studied.